IMPLEMENTASI SISTEM EDUTAINMENT PADA PELAJARAN MATEMATIKA UNTUK KELAS 6 SD BERBASIS WEB (Studi Kasus Siswa dan Siswi SDN Kadu IV Curug) - Sri Mulyati; . Nurasiah; Adi Widodo (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2016)
ABSTRACTEducation mathemathic is the one of hard education for students specially for student’s atSD Negeri Kadu IV Curug. Convensional system is method for study mathemathic at SDNegeri Kadu IV Curug, there are come to the class, learning, look a book, and listen’s ateacher in class. When teacher give homework for students, student have absence difficultfor does her homework because he doesn’t understand a teory. Because of that studentsneed alternative method for studing mathemathic for solve the problem. Where the purposeof writing this thesis itself is building edutainment system mathemathic for student class 6elementary school which based is web. The methodologi used for the design of this system iswaterfall. The proccesof waterfall are analysys, design, coding, testing and maintanance.Programming language and database for build the system are PHP and MySQL.Key Words : Education Mathemathic, Edutainment System, web